2020
DOI: 10.4102/ajlm.v9i1.1182
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in whole blood stored for transfusion at Bungoma County Referral Hospital, Kenya

Abstract: Background During storage, transfusion blood may undergo a series of biochemical changes that could pose risks to patients when used. It is important therefore to monitor biochemical changes that may reduce survival or function of stored blood cells. Objective This study assessed biochemical changes in whole blood stored for transfusion at Bungoma County Referral Hospital in the western region of Kenya between February 2019 and August 2019. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Haemoglobin level estimation demonstrated a slight decrease from day 0 to Day 28 (from 14.2±1.7 to 12.1±1.4) similar to several previous studies (7,8). A study recorded a slight increase in Hemoglobin levels.…”
Section: Table 5 the Sodium Level In The Storage Period From Day 0 To...supporting
confidence: 88%
See 4 more Smart Citations
“…Haemoglobin level estimation demonstrated a slight decrease from day 0 to Day 28 (from 14.2±1.7 to 12.1±1.4) similar to several previous studies (7,8). A study recorded a slight increase in Hemoglobin levels.…”
Section: Table 5 the Sodium Level In The Storage Period From Day 0 To...supporting
confidence: 88%
“…A significant decrease of WBC was observed from Day 0 to Day 28 i.e. 7.6 The present study also showed a decrease in mean RBC count from 1st day to the 28th day which is to a study done by Marabi PM et al, 2020; Chaurasiya AK et al, 2022; Shrivastava P, Dutta S 2020; (7,8,10). In contrast to the findings of our study, Batham N. et al recorded no significant elevation in RBC count during the storage of 35 days (11).…”
Section: Table 5 the Sodium Level In The Storage Period From Day 0 To...supporting
confidence: 86%
See 3 more Smart Citations